Using two-photon excitation methods for determination of Ca2+ in contamination with protein - full length research paper. - Muhammad Noor, Ahmad Shukri; Inami, W.; Miyakawa, Atsuo; Kawata, Yoshimasa (2011)
Three emission wavelengths from two-photon excitation techniques were use to determinefree Ca2+ using a new analytical calculation. This was achieved by considering theinteraction of protein with free Ca2+ and indo-1 in protein contaminated sample. The emissions obtained from the excitation with the dissociation constants were used in the calculation. Agreement values of the Ca2+ from the calculation with the known Ca2+ buffer solution used for the measurement was obtained for various Ca2+ and protein concentration. The analytical analysis shows that dissociation constants for each binding’sdeviation errors are small to affect free Ca2+ determination. This would provide an accurate measurement of free Ca2+ in biological cells than the typical two emission wavelength processes. Furthermore, using two-photon excitation methods, deep inside cells observation of free Ca2+ are possible using the methods introduced.